Systematic Mapping of Recent Scientific Production on Government Communication (Intercom - Brazilian Journal of Communication Sciences, 2024)
Government communication in contemporary societies is characterized, in addition to the dissemination of information, by transparency, collaboration, and encouragement of the active participation of citizens in public policies. The objective is to analyze the scientific production relative to government communication from 2018 to 2022 through a systematic mapping, a type of bibliometric study, based on the articles available in the Scopus and Web of Science databases. We concluded that the theme presents a consistent number of publications with a growing trend and is present in research worldwide but with little collaboration between countries. No authors or even journals that concentrate on many publications were identified. We identified emerging themes beyond the pandemic context: public policy, government, public opinion, and social media. The article contributes to the critical development of the area of government communication.
Keywords: Public communication; Public information; Public Governance; Digital democracy; Citizen participation